2009
DOI: 10.2217/pgs.09.71
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C9*8 is Prevalent Among African–Americans: Implications for Pharmacogenetic Dosing

Abstract: Aims Although the frequencies of pharmacogenetic variants differ among racial groups, most pharmacogenetic algorithms for genotype-guided warfarin dosing only include two CYP2C9 alleles (*2 and *3) and a single VKORC1 allele (g.-1639G>A or g.1173C>T) commonly found among Caucasians. Therefore, this study sought to identify other CYP2C9 and VKORC1 alleles important in warfarin dose variability and to determine their frequencies in different racial and ethnic groups. Materials & methods The CYP2C9 and VKORC1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 54 publications
8
92
1
Order By: Relevance
“…Since CYP2C9 plays a role in the metabolism of arachidonic acid, a modulator of vascular tone and cardiovascular homeostasis, the increased frequency of defective alleles may be postulated to contribute to the high levels of cardiovascular disease in northern Africa, a concept supported previously by other groups [44,45]. Based on a handful of studies reported to date, CYP2C9*8 may also be regarded as a contributor to decreased drug clearance in populations of African origin, where it is present at allelic frequencies ranging from 1-12% [8,46,47]. When investigating the variants that contribute to variability in warfarin metabolism, it has been reported that this allele, together with CYP2C9*5, *6 and *11, may contribute to up to 30% of the variability in Africa-Americans [48].…”
Section: Cyp2c9 and The Management Of Cardiovascular/circulatory Disementioning
confidence: 76%
“…Since CYP2C9 plays a role in the metabolism of arachidonic acid, a modulator of vascular tone and cardiovascular homeostasis, the increased frequency of defective alleles may be postulated to contribute to the high levels of cardiovascular disease in northern Africa, a concept supported previously by other groups [44,45]. Based on a handful of studies reported to date, CYP2C9*8 may also be regarded as a contributor to decreased drug clearance in populations of African origin, where it is present at allelic frequencies ranging from 1-12% [8,46,47]. When investigating the variants that contribute to variability in warfarin metabolism, it has been reported that this allele, together with CYP2C9*5, *6 and *11, may contribute to up to 30% of the variability in Africa-Americans [48].…”
Section: Cyp2c9 and The Management Of Cardiovascular/circulatory Disementioning
confidence: 76%
“…18,30 Unfortunately, the VKORC1, CYP2C9 and CYP4F2 genes remain poorly characterized in many population groups, and there may be other variants within these genes affecting warfarin dose that would be relevant to include in the pharmacogenetic-based dosing algorithms. For example, Scott et al 43 recently described a variant (CYP2C9*8) present in an African-American male with a lower than predicted warfarin dose (based on prior genotyping of CYP2C9 and VKORC1 alleles). On further characterization of this variant in an African-American sample, the authors reported that CYP2C9*8 is the most frequent variant in this sample, and predicted that incorporation of this polymorphism in pharmacogenetic-based dosing algorithms could potentially reclassify the predicted metabolic phenotypes of almost 10% of African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…41,42) Furthermore, it is recognized that CYP2C9*5, CYP2C9*8, CYP2C9*11, and CYP2C9*13 reduce the clearance of warfarin in humans. [42][43][44][45][46] However, there are still many unknown aspects in terms of the effects of CYP2C9 gene polymorphism on the pharmacokinetics of warfarin.…”
Section: Cyp2c9mentioning
confidence: 99%